Study hydrogen embrittlement and determination of E110 fuel cladding mechanical properties by ring compression testing. (December 2018) - Namburi, H K; Ottazzi, L; Chocholousek, M; Lomonaco, G; Gavelova, P; Krejci, J
Abstract: Zirconium based alloys are commonly used as material for fuel claddings in the light water reactors. Claddings act as first metallic barriers against loss of fission products during the nuclear power plant operation, intermittent storage or final dry storage. The integrity of claddings is always critical issue during reactor operation and during storage of spent fuel. In this work, ring compression testing method developed was applied to study hydrogen embrittlement, to evaluate the stress-strain behaviour and hoop fracture properties of E110 (Zr-based) fuel claddings. The results show that the collapse load and the tensile strength values depend strongly on hydrogen concentration. In particular, tensile strength experiment data shows significant change in its trend after reaching the maximum hydrogen solubility limit.